Qualitative Exploration of the Influence of Domestic Violence on Motherhood in the Perinatal Period - Lévesque, Sylvie (Journal of family violence, 2022)
The perinatal period may include domestic violence (DV). In this study, the perinatal period extends from the start of pregnancy to the end of the child’s second year of life. DV places the safety of both mother and child at risk and undermines the mother–child attachment bond. In this article, we look at the challenges for motherhood in a context of domestic violence during the perinatal period (DVPP). In semi-directed interviews, 17 mothers shared their stories of DVPP. Interview questions focused on the trajectory of DVPP, perceptions and occupation of motherhood within two years of childbirth and the associated challenges. Data were analyzed using thematic analysis and discussed in a feminist conceptual framework and a parental theoretical model. DVPP negatively influences the experience and practice of motherhood, in addition to increasing parental responsibility to protect the child. Three main themes were noted: 1) A parental experience impoverished by the context of DVPP, caused by an increase in tasks, a weakened bond with the child and a loss of self-confidence; 2) Parenting responsibility in a context of DVPP is expressed as greater vigilance and the need to protect the child from violence; and 3) Parenting practices: the children as targets and victims of violence, resulting in additional child needs that mothers must meet. The results underscore the need for early detection of DVPP and a trauma-informed approach in health services. Specialized support services should be provided to help mothers cope with violence.